Peran Dukungan Keluarga Terhadap Kesehatan Mental Remaja Pelaku Pernikahan Dini - Sopi Meirani; M. Fahli Zatrahadi; Miftahuddin Miftahuddin (Jurnal Keluarga Sehat Sejahtera, 2026)
Adolescence is vulnerable to various mental health issues, especially for teenagers who marry early. Early marriage can cause psychological stress, changing social roles, and responsibilities that adolescents are not fully prepared for. This study investigates the role of the family in maintaining the mental health of adolescents who marry early. Data were obtained thru qualitative descriptive research with a literature study approach from various relevant sources, such as books, health organization reports, and national and international scientific journals. Identification, classification, interpretation, and synthesis of data are content analysis methods used to analyze the data. Studies show that families can help adolescents who marry early maintain their mental health thru open communication, emotional support, positive parenting, warmth in family relationships, and social and economic support. Conversely, family conflict and lack of support increase the risk of stress, anxiety, and other psychological disorders. These findings indicate that family involvement is crucial in helping adolescents adjust to new roles and improve psychologically.